A case of unilateral acute hypertensive uveitis in a child. Issue 1 (January 2022) - Marrani, Edoardo; Venturini, Elisabetta; Danti, Gioia; Galli, Luisa; Caputo, Roberto; de Martino, Maurizio; de Libero, Cinzia
A 6-year-old boy was referred to our hospital for sudden blurring vision in the left eye. An ophthalmological evaluation showed white endothelial keratic precipitates and increased intra-ocular pressure. To our knowledge, this is the first reported case of hypertensive uveitis in children under 10 years of age and we also discuss the role of Epstein-Barr virus as a possible infectious trigger.